Sustainability Fund for livelihood activities in post project period - Mathur, I. J.; Intodia, S. K.; Agarwal, S. K. (Indian Farming, 2015)
In the NAIP sub-project sanctioned to MPUAT, Udaipur under component Sustainable Rural Livelihood Security, a concept of Sustainability Fund was introduced to ensure post project sustainability. For each technology/input some contribution was collected from farmers in each cluster. Up to 31 March, 2014, the clusters (10) have Rupees 344 lakhs in Sustainability Fund Account. The SF will ensure sustainability of the project activities and farmers who have not got full advantage of the sub – project will also be benefited.